Pengaruh Pemberian Mulsa dan Irigasi pada Pertumbuhan dan Hasil Bawang Merah (Allium cepa L. var. agregatum) - Zuliati, Septiarini; Eko Sulistyono; Heni Purnamawati (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2020)
Soil water availability is maintained by providing irrigation and mulching. This study aimed to develop efficient irrigation volume on various types of mulch for growing shallot variety of Bima Brebes. The study was arranged in a randomized complete block design with two factors and three replications. The first factor was the level of irrigation based on pan evaporation, consisting of six levels: 0.25 Eo, 0.50 Eo, 0.75 Eo, 1.00 Eo, 1.25 Eo, and 1.50 Eo. The second factor was the type of mulch, consisting of three levels: without mulch, black silver plastic mulch, and rice straw mulch. The interaction between irrigation volume and mulch type increased plant height, number of leaves, number of shoots, root volume, number of root, total dry weight, bulb diameter, and bulbs weight. The combination of irrigation volume 1.50 Eo with plastic mulch produced the highest weight of bulbs similar to the combination of irrigation volume 0.50 Eo and 0.75 Eo on plastic mulch and irrigation volume 1.00 Eo and 1.50 Eo without mulching. A combination of irrigation volume 0.50 Eo and plastic mulch was recommended for water use efficiency and less use of water. Keywords: bulb diameter, evaporation, black silver plastic mulch, straw mulch